Asuhan Kebidanan Continuity of Care (COC) pada Ny K.N.F.T Umur 29 Tahun di Puskesmas Kota Atambua - Aplonia Lou Manu; Afriyani, Luvi Dian (Universitas Ngudi Waluyo, 2024)
Maternal Mortality Rate (MMR) is an important indicator of the level of public health. MMR describes the number of women who die per 100,000 live births (KH), from a cause of death related to pregnancy disorders or their treatment (excluding accidents or incidental cases) during pregnancy, childbirth and in the postpartum period (42 days after giving birth) so that comprehensive care is provided to prevent maternal deaths during pregnancy, childbirth and postpartum (Indonesian Health Profile, 2018). The maternal mortality rate in Belu Regency in 2019 was 5 cases, in 2020 there were 12 cases, in 2021 there were 7 cases, in 2022 there were 6 cases, in 2023 there were 7 cases, for 2024 from January to now there were 3 cases. The highest cause of death occurs when the mother gives birth due to preeclampsia/eclampsia, bleeding, placental abruption, etc. The Infant Mortality Rate (IMR) in Belu Regency in 2019 was 80 cases, in 2020 there were 66 cases, in 2021 there were 53 cases, in 2022 there were 48 cases, in 2023 there were 49 cases with the highest causes being births with low birth weight babies, asphyxia , congenital abnormalities and other causes include congenital heart disease, sepsis and others. From the data above, it can be seen that the causes of maternal and infant deaths can occur during pregnancy, childbirth, BBL and postpartum birth control. So comprehensive and sustainable care is care to provide care by knowing and understanding the mother to foster mutual trust so that it is easier to provide services that suit the mother's needs by providing comfort and support, not only during pregnancy and after delivery, but also during delivery and Birth is very necessary for mothers. This care is provided to mothers during pregnancy, childbirth, postpartum and newborns to prevent complications that can cause death. The services provided are comprehensive midwifery services starting from pregnancy, childbirth, postpartum, newborns and family planning. So the author carries out midwifery care with the title